An Examination of Intimacy and Loneliness in Sex Offenders - Seidman, Bonnie T.; Marshall, William L.; Hudson, Stephen M.; Robertson, Paul J. (Journal of interpersonal violence, 1994)
Two studies are reported examining intimacy and loneliness in sex offenders and various control subjects. Sex offenders were both more lonely and deficient in intimacy than other offenders and community controls. Intimacy seemed to be the most important deficit among the sex offenders with the rapists and child molesters being the most deficient. The results are discussed in terms of their relevance for theory and clinical practice